Synthesis and Characterization of Graphene Oxide and its Composites. (1st August 2022) - Parkash, Anand; Solangi, Nizamuddin; Solangi, Sorath; Larik, Rimsha; Kumar, Sunil; Kumar, Raj
Abstract : The chemical approach synthesis of graphene oxide easily with four to five layers. Pt nanoparticles are anchored to graphene oxides by lattice defects and functional groups like carbonyls, epoxides, hydroxyls, etc. The electrical characteristics of these graphene oxide sheets were enhanced. The shape and physical properties of these graphene materials are comparable, but because of variations in the number of oxygen functions, significant changes in electrical conductivity, graphitization, and stability have been seen.